2021
DOI: 10.3390/su14010248
|View full text |Cite
|
Sign up to set email alerts
|

Experienced Well-Being in the Rural Areas of the Srem Region (Serbia): Perceptions of the Local Community

Abstract: The sustainability of rural settlements in Serbia has become the main focus of strategic rural development planning. Although it is still difficult to measure the quality of life of the citizens of the Republic of Serbia, preliminary results show that it is necessary to go beyond the GDP as the only or one of its most important indicators. A multidimensional approach and analysis at the local level is necessary for more comprehensive insight into quality of life in order to avoid erroneous or simplified conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…The study was based on a survey questionnaire previously used in the area of Srem, one of the three regional wholes in Vojvodina [93]. For this questionnaire, it was confirmed that the "statements have a relatively high internal consistency" [93] (p. 10).…”
Section: The Instrument and Proceduresmentioning
confidence: 94%
See 2 more Smart Citations
“…The study was based on a survey questionnaire previously used in the area of Srem, one of the three regional wholes in Vojvodina [93]. For this questionnaire, it was confirmed that the "statements have a relatively high internal consistency" [93] (p. 10).…”
Section: The Instrument and Proceduresmentioning
confidence: 94%
“…A more complex and all-encompassing view of quality of life requires a multi-dimensional approach, which decreases the possibility for error. That was why well-being in this paper was analyzed through specially selected indicators and the course of six dimensions (place of residence, educational opportunities, culture and sport, public services, healthcare, and economic opportunities), each of which was represented by a sequence of indicators [93].…”
Section: Measuring Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…After all, it is the government's role to provide people with fair, immediate, and future access to resources and to achieve prosperity [10]. It is important to understand important factors in preserving the tradition of heritage during sustainable development [11]. This current study examines how to develop such synergy along the heritage attractions of China's Grand Canal.…”
Section: Theoretical Background 21 Linear Heritage Tourismmentioning
confidence: 99%
“…The life satisfaction of rural households is of major concern. In Ðerčan et al [19], based on the five dimensions of health, education, culture, sports, and community, the quality of life of local farmers was investigated. Li et al [20] used the ordered Probit model to examine the differences in life satisfaction of farmers and found that the life satisfaction of poor households was generally lower than that of middle and wealthy households.…”
Section: Introductionmentioning
confidence: 99%